The Potency of Cratoxylum arborescens Blume (Geronggang) and Combrecarpus rotundatus Dans (Tumih) as Natural Regeneration in Degraded Tropical Peat Swamp Forest - David Suwito; Suratman; Erny Poedjirahajoe (Pusbindiklatren Bappenas, 2021)
The massive forest fire disasters have left an enormous area of ​​degraded peatland. This study aims to analyze the performance of two species, namely C. arborescens and C. rotundatus, as the natural regeneration post forest fires. This research was conducted in 5 different locations that experienced severe fires in 2006. We made a total of 25 plots for each location to measure biodiversity at four growth levels. We analyzed the data with vegetation analysis formulas from Magurran. The results show that at the tree growth level, C. rotundatus can withstand the fires in 2006 and is currently still growing in more significant numbers than C. arborescens. At the pole, sapling, and seedling growth levels, these species perform well as natural regeneration species with many individuals, but C. arborescens is a bit more dominant. Both species are suitable for natural regeneration after fires in degraded peat swamp forests based on survived and existing individuals. On the other hand, both species could not improve the vegetation diversity in the whole ecosystem. These two species can be the option for natural regeneration if there a limited budget and the degraded areas are in a very remote location.